2020
DOI: 10.3390/f11111129
|View full text |Cite
|
Sign up to set email alerts
|

Tree Allergen Pollen-Related Content as Pollution Source in the City of Ourense (NW Spain)

Abstract: Allergies became a major public health problem, identified as an important global pandemic with a considerable impact on the worldwide economy. In addition, a higher prevalence of pollen Type I sensitization cases in urban environments in comparison with the rural territories was detected. Our survey sought to assess the main biological pollution episodes caused by the aeroallergens of the major allergenic tree species in urban environments. A Hirst-type volumetric device was used for pollen sampling and a Bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…A similar trend was also observed for the total pollen and temperature in Carlow in April 2018. Although many tree pollen types have been shown to possess a generally positive correlation with temperature, Fraxinus pollen has been shown to illustrate a negative association (Álvarez-López et al, 2020 ). A significant negative relationship with temperature was also seen for Urticaceae pollen, from Carlow 2019, likely depicting the effects of heat stress on pollen release (Emberlin & Norris-Hill, 1991b ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar trend was also observed for the total pollen and temperature in Carlow in April 2018. Although many tree pollen types have been shown to possess a generally positive correlation with temperature, Fraxinus pollen has been shown to illustrate a negative association (Álvarez-López et al, 2020 ). A significant negative relationship with temperature was also seen for Urticaceae pollen, from Carlow 2019, likely depicting the effects of heat stress on pollen release (Emberlin & Norris-Hill, 1991b ).…”
Section: Discussionmentioning
confidence: 99%
“…After conducting research over a period of two years (2017 and 2018), it was found that plane and alder are the species with the highest number of days with an average potential risk of allergies (a total of 22-27 days for both years). Also, plane, along with birch, have the most days (30-31 days) in total for the two years with a high average amount of wind-borne pollen [33].…”
Section: Disadvantages Of Platanus X Acerifoliamentioning
confidence: 99%
“…Alan et al (2020), Á lvarez-López et al (2020,Beck et al (2013),Brito et al (2011), Buters et al (2008), De Linares et al (2010, 2019), Fernández-González et al (2013, 2019a,Galan et al (2013),Gong et al (2017), Jochner et al (2015,Plaza et al (2016), Rodríguez-Rajo et al (2011), Schäppi et al (1997b, Wang et al (2013a, b) Meteorological factors are not associated with potency Alcazar et al (2015) Altitude affects pollen potency Jochner et al (2015) Proximity to ocean affects pollen potency Fernández-González et al (2019a) Long distance dispersal of pollen can affect pollen potency because potency varies in pollen from different locations Alan et al (2020), Á lvarez-López et al (2020), Buters et al (2012), Fernández-González et al (2019a), Galan et al (2013) and Jochner et al (2015)Ozone exposure increases pollen potencyBeck et al (2013) …”
mentioning
confidence: 99%